PENGARUH PENDIDIKAN GIZI TERHADAP PENGETAHUAN DAN PERILAKU KONSUMSI SERAT PADA SISWA - Ratu Ayu Dewi Sartika (Universitas Negeri Malang, 2011)
Abstract: Effect of Nutrition Education on Knowledge and Behavior of Fiber Consumption among Primary School Students. This study aims at examining the effect of nutrition education on knowledge and behavior of fiber consumption among primary school students. The design employed was quasi-experimental research design with pre and post intervention. The results indicate that there was increased knowledge as indicated by the scores of students after intervention (p